Frequency-Selective Surfaces to Enhance Performance of TEM Horn Antenna - Belen, Mehmet Ali; Sharipov, Zafar; Mahouti, Peyman; Demirel, Salih; Gunes, Filiz (IEEE, 2015)
This article presents the analysis and investigation of the effect of loading a TEM horn antenna with a frequency selective surface (FSS) of finite size. It is simulated on FR4 (lossy) of relative permittivity 4.4, thickness 1.58mm and loss tangent 0.0035. This structure is called a filtering antenna (filtenna). Basically it is applied for filtering and minimizing the interference and noise in the desired band. The filtration is carried out using a finite FSS of double square loop of overall dimensions 20mmx20mm. The structure is simulated using CST MWS.
Keywords: Frequency-Selective Surfaces; Horn Antenna; Filtenna; Engineering; Telecommunications